A Fast and Practical Method for Animating Particle-Based Viscoelastic Fluids - Takamatsu, Kenji; Kanai, Takashi (International Journal of Virtual Reality, 2011)
This paper proposes a practical technique for fast animation of materials such as viscoelastic fluids. A fast animation of such materials is desperately desirable especially for real-time applications such as games. We compute the behavior of viscoelastic fluids approximately instead of the exact simulation by combining two well-established approaches, Smoothed- Particle Hydrodynamics and Shape Matching. This enables fast and stable computations. A combination is done by a simple linear interpolation of velocities. A variety of materials between a fluid and an elastic solid can be represented by changing only a parameter of linear interpolation. We also propose how to bring our approximate method closer to the actual motions of viscoelastic fluids including merging or splitting of objects. We demonstrate a high-speed performance of our method with presenting several interesting results.